2012
DOI: 10.1017/s1751731111002096
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three fluorescent CYP3A substrates in two vertebrate models: pig and Atlantic salmon

Abstract: We investigated in vitro inhibitory effects of ketoconazole (KTZ) on cytochrome P450 activity in microsomes from pigs and Atlantic salmon. The following enzymatic reactions were studied: 7-benzyloxyresorufin and 7-ethoxyresorufin O-dealkylation (BROD and EROD, respectively), 7-benzyloxy-4-trifluoromethylcoumarin O-debenzylation (BFCOD) and 7-benzyloxyquinoline O-debenzylation (BQOD). KTZ was a potent non-competitive inhibitor of BROD and BQOD in the microsomes from pigs, whereas in the microsomes from Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…These inhibitors have previously been shown to have an effect on the activities of CYP450 isoforms in microsomal or hepatocyte assays Rasmussen et al, 2011b;Zlabek and Zamaratskaia, 2012). The incubations were performed in the presence of 0.125, 1.25 and 12.5 µM of the specific inhibitor, except for E2 (used concentration 0.002, 0.02 and 0.2 µM) and quercetin (16, 32 and 128 µM).…”
Section: Microsomal Incubations With Cyp450 Isoform Inhibitorsmentioning
confidence: 99%
“…These inhibitors have previously been shown to have an effect on the activities of CYP450 isoforms in microsomal or hepatocyte assays Rasmussen et al, 2011b;Zlabek and Zamaratskaia, 2012). The incubations were performed in the presence of 0.125, 1.25 and 12.5 µM of the specific inhibitor, except for E2 (used concentration 0.002, 0.02 and 0.2 µM) and quercetin (16, 32 and 128 µM).…”
Section: Microsomal Incubations With Cyp450 Isoform Inhibitorsmentioning
confidence: 99%
“…Both BROD and BFCOD are considered to be marker reactions to estimate the CYP3A activity. Our previous study showed that these reactions were strongly inhibited by ketoconazole, a well‐known inhibitor of CYP3A (Zlabek and Zamaratskaia 2011). Interestingly, these reactions showed differences in response to testicular steroids.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of CYP3A were estimated as activities of BR O-dealkylase (BROD) and BFC O-debenzylase (BFCOD) (Zlabek and Zamaratskaia 2011). CYP2C activity was estimated using two substrates, tolbutamide and diclofenac.…”
Section: Preparation Of Hepatic Microsomes and Enzymatic Activitymentioning
confidence: 99%
“…The effect of ketoconazole on xenobiotic metabolism is multifaceted. Ketoconazole can modulate mRNA, protein expression and catalytic activities of several fishCYP450 isoforms (Hasselberg et al, 2005;Hegelund et al, 2004;Zlabek and Zamaratskaia, 2012). Clotrimazole was also shown to affect PXR (Moore et al, 2002) and AhR (Navas et al, 2004a).…”
Section: Azolesmentioning
confidence: 99%
“…Clotrimazole was also shown to affect PXR (Moore et al, 2002) and AhR (Navas et al, 2004a). A note of caution should be introduced becausein vitro studies demonstrated inhibition of CYP1A and CYP3A by clotrimazole (Burkina et al, 2013) and by ketoconazole (Hegelund et al, 2004;Zlabek and Zamaratskaia, 2012). It is evident that although the activities of CYP1A and CYP3A are regulated via AhR and PXR, they can also be directly controlled by non-receptor mediated mechanisms.…”
Section: Azolesmentioning
confidence: 99%